HARNESSING THE POWER OF G-PROTEIN COUPLED RECEPTOR-120 IN REDEFINING INSULIN RESISTANCE AND INFLAMMATION MANAGEMENT IN POLYCYSTIC OVARY SYNDROME - NEETI PATEL; IVVALA ANAND SHAKER; KANDARP PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aims to evaluate serum G-Protein Coupled Receptor 120 (GPR120) levels and its association with anti-inflammatory cytokine Interleukin-10 (IL-10), Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), and female reproductive hormones in PCOS subjects as it is disorder of affecting reproductive women with complex combination of symptoms like excess androgens, polycystic ovaries, ovulatory dysfunction, Insulin resistance and chronic low-grade inflammation. Methods: In a cross-sectional study carried out at the tertiary care hospital of the South Gujarat district between March 2023 to December 2024. Using a convenience sampling technique, a total 248 women (124 PCOS and 124 age-matched healthy controls) were assessed for markers like Serum GPR120, IL-10, insulin, adiponectin, LH, FSH, testosterone, and anthropometric parameters. Student’s t-test (p-value) was applied for significance and Pearson’s correlation (r-value) for finding the association between parameters as a part of statistical analysis. Results: Elevated serum LH:FSH, Testosterone, Insulin, HOMA-IR, and significantly decreased levels of GPR120, IL-10, and adiponectin were reported in PCOS subjects as compared to the non-PCOS group. GPR120 showed a strong positive correlation with Adiponectin (r = 0.925), IL-10 (r=0.681) and a negative correlation with BMI (r=-0.325), WHR (r=-0.516), Testosterone (r=-0.539), Insulin (r=-0.085) and HOMA-IR (r=-0.087) in women with PCOS disorder. Conclusion: Lower levels of GPR120, and its strong correlation with HOMA-IR and inflammatory markers, suggest its key role in the pathophysiology of PCOS. GPR120 may serve as a novel therapeutic approach for alleviating metabolic and inflammatory disturbances in PCOS.